Effect of health education on awareness and practices of breast self-examination among females attending a charitable hospital at North Karachi - Zohra Jabeen; Nighat Shah; Zaeema Ahmer; Sulhera Khan; Amir Hussain Khan; Marium Khan (Journal of the Pakistan Medical Association, 2021)
Objective: The objective of this study was to compare the effectiveness of health education as an intervention to promote BSE among intervention and non-intervention group presenting in a low resource setting at North Karachi Methodology: This Quasi-experimental study was conducted from January-August 2018 in a charitable hospital in Karachi after taking ethical approval by the Institutional Review Board of Jinnah Sindh Medical University and relevant approvals from the hospital authorities. This study recruited 172 eligible women by dividing them into intervention (n=86) and control (n=86) groups from a low resource setting in Karachi. Demographic variables were collected through pretested questionnaire by interview. Intervention group then received health education regarding carcinoma of breast, importance of BSE and monthly motivation to perform BSE through cell phone. The questionnaire was again filled after 6 months of intervention. Control group was also given health education sessions upon completion of study. Results: Results revealed that both groups were similar initially. After 6 months females in intervention group showed significant (p=<0.001) improvement in knowledge and performance of BSE from 44.2% to 88.4% but there was no change in control group. Being in intervention group (RR=2.714, 95% CI= 1.760 - 4.186, p=0.001) and education (RR=0.573, 95% CI= 0.361 - 0.910, p=0.018) showed positive association with BSE performance. Upon adjusting with age, marital status, family history and education, intervention group (RR=2.570, 95% CI= 1.654 - 3.992, p= 0.001) remained significant while education (RR=1.466, 95% CI =0.910 - 2.363, p=0.116) became insignificant. Continuous...